¿Rompiendo con el pasado? La cooperación al desarrollo belga en el cambio de siglo - Holvoet, Nathalie; Renard, Robrecht (Revista Española de Desarrollo y Cooperación, 2023)
The article deals with the evolution of Belgium aid polices during the 90’s and a description of its main actors, instruments as well as sectoral and geographical aid allocation. Belgium cooperation in the 90’s assisted to the end of the Cold War and its effects on Central Africa, an emerging critical public opinion about the role of aid and the growing role of Decentralised Co-operation of its two main communities, the Francophone and the Flemish, all these issues affecting the reforms pursued by the different governments during this decade